Effect of pre-treatments on the germination of jasmin box (Phillyrea latifolia) seeds in Greece - Spyroglou, Gavriil; Radoglou, Kalliopi (BOSQUE, 2017)
The major problem in seedlings production of jasmin box (Phillyrea latifolia) is the poor and irregular germination due to seed dormancy. The objective of the present study was to evaluate methods of seed pre-treatments to increase germination. The effect of different solutions of KOH and NaOH, wood ash lye, GA3 and cold or warm stratification on germination were evaluated. Sets of four replicates of 25 seeds were soaked for 24 hours in KOH and NaOH solutions of 0.2, 0.5, 1 and 2 %, in wood ash lye solutions of 33, 66, 133, 166, 532 g L-1 and in GA3 solutions of 250, 500, 1000, 2,000, 3,000 mg L-1. A control set of seeds was imbibed in water for 48 hours. All sets went through zero, two, four and six months of cold (2-4 °C) or warm (15 °C) stratification. The seeds were incubated in petri dishes filled with moistened sand, at two alternating temperatures (20/15 and 30/20 °C) with a light period of 16 hours. From the results we conclude that: Chemical pre-treatments with KOH and ash lye and warm stratification increased germination to 96 %. Treatment with water and warm stratification also increased germination to 79 %. Treatment with 250 mg L-1 GA3 and six months warm stratification increased germination to 70 % while higher concentrations had a negative effect. Cold stratification did not break dormancy. Optimum germination temperature in a growth chamber was 15-20 °C, while temperature at 20-30 °C inhibited germination.